(untitled) (Fiep Bulletin - online, 2020)
An active lifestyle provides several health benefits, whether social or psychological, considering that these mechanisms are considered fundamental points for a good quality of life and independence of the elderly. The objective of this study was to investigate the quality of life of elderly people practicing different types of physical activities. The research presented a descriptive characteristic with a quantitative approach. The population of approximately 100 practitioners was composed of users of the “Active Life Project” located in the city of Patos - PB, and the sample consisted of 30 elderly aged 60 to 90 years, average of 70.0 ± 7.1 of them. Which 10 of each modality practiced: Water aerobics, Gymnastics and Dance. To assess the quality of life of the elderly, the SF-36 quality of life questionnaire was used as an instrument. It was a multidimensional questionnaire consisting of 36 items grouped into two components called physical and mental distributed in eight domains: functional capacity, physical aspects, emotional aspects, mental health, social aspects, vitality, pain and general perception of health. The data were analyzed using the Excel for Windows 17 program. The dominance of the practiced mode of dance is verified, where the aspect of physical capacity did not prevail, standing out in the others: social aspects (86.3), mental health (81.6 ), vitality (74.5) and general health (71.5), and only the pain level (62) is of concern, since according to the Raw scale, the table reverses the closer to 100 worse. the domain presents itself. Physical activity is a determining factor in the healthy aging process, enabling the elderly population to go through this process with better quality of life.